Update on the pharmacotherapy for myelodysplastic syndromes. (September 2014) - Duong, Vu H; Komrokji, Rami S; List, Alan F
<x xml:space="preserve">Abstract</x> Introduction: For many decades, myelodysplastic syndromes (MDS) were a poorly understood disease group with no approved therapies, and patient management largely relied upon supportive care and intensive chemotherapy. The last decade has seen many scientific and therapeutic advances culminating in the US FDA approval of three drugs for the treatment of these complex malignancies: lenalidomide, azacitidine and decitabine. Areas covered: This review summarizes the major prognostic risk models that guide treatment decisions and examines the available literature on the mechanism of action and efficacy of each of the approved agents. The authors also discuss evidence supporting the use of other therapies that have entered the standard of care including growth factors, immunosuppressive therapy and stem-cell transplantation. Expert opinion: While significant progress has been made in understanding the molecular basis of MDS, much of this has yet to translate into therapeutic benefit. Each of the available treatment modalities has shortcomings, and both combination strategies and novel agents are under investigation in clinical trials to improve outcomes.